IMPLEMENTASI KURIKULUM 2013 MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - M. Muslim (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2022)
The purpose of this study was to determine the implementation of the 2013 curriculum in Subjects to determine the supporting and inhibiting factors in the implementation of the 2013 curriculum. The method in this study used a type of qualitative research by taking the background of an Islamic Religion teacher. Data collection techniques were carried out through interviews, observations and documentation. The results of the study show that the implementation of the 2013 curriculum carried out by Islamic Religion education teachers at Madrasah Aliyah Mathla'ul Anwar Pusat Menes has been going well even though at the implementation level it has not been fully implemented because everything is a process which must run from the start. This can be seen in terms of planning, implementing, and evaluating learning that is in accordance with the principles of implementing the 2013 curriculum.